A conceptual framework for ex ante valuation of ecosystem services of brownfield greening from a systematic perspective. Issue 1 (16th December 2020) - Zhong, Qicheng; Zhang, Lang; Zhu, Yi; Konijnendijk van den Bosch, Cecil; Han, Jigang; Zhang, Guilian; Li, Yuezhong
ABSTRACT: Introduction: Although Brownfield greening (BG) can be a crucial solution to green space deficiency in dense urban areas, the potential benefits of different BG initiatives have rarely been quantitatively pre-evaluated. Here, the concept and main features of BG and its costs and benefits are firstly depicted. Next, a conceptual framework is presented which combines ecosystem service (ESS) valuation, economic cost-benefit analysis, and spatial pattern analysis. The framework is used to perform ex ante valuation of the ESS value of BG in Xuhui District, Shanghai. Outcomes: The scenario comparison results show that it can spatially reflect a closer-to-reality value of ESS at the urban scale instead of a theoretical value at the site scale. The ultimate values of ESS (After economic and landscape adjustments) in the composite scenario is more than 21% higher than those in the full-eco scenario, whereas the initial values of ESS (before the adjustments) in the former was 14% lower than those in the latter. These results suggest that a considerable part of brownfield greening projects need to be implemented in the more populated and economically vibrant areas instead of solely in the ecological construction zone, thereby correspondingly providing more cultural and regulation services and forming a better urban green space network. Conclusion: The framework provides a simple, science-based, and feasible tool for making BG decisions from a systematic perspective in dense urban areas. It can help meet the need for applying ESS knowledge to BG-based green space planning and policy making in the context of urban sustainable development.